Implementation of the Constraint Satisfication Problems Method in Genetic Algorithms for Course Scheduling Systems - Isa Martinus, Agust; Budi Hartono, Mukhamad; Wicaksono, Freddy (Ann Publisher, 2023)
The creation of class schedules requires a high level of precision and focus to generate the best possible timetable. A schedule with the best solution can provide comfort for both faculty and students, thus enhancing the quality of early meetings during classes. However, in the engineering faculty of Muhammadiyah University Cirebon, classes often do not start simultaneously with other faculties due to the manual scheduling process. Addressing this issue, a system is needed to automate the creation of class schedules. By implementing the Constraint Satisfaction Problems method to impose constraints before evaluating the fitness values in the Genetic Algorithm, it can assist in searching for the best solutions in accordance with the scheduling requirements of each program in the Engineering faculty. The results of black box testing on the system, item code 06, demonstrate that the system can produce schedules that comply with the requirements of each program in the faculty.